1959
DOI: 10.1017/s0021859600036601
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of irrigated pastures by dairy cows. I. A comparison of rotational and strip grazing

Abstract: 1. An experiment was carried out from 1 August 1953 to 31 July 1955 to compare strip grazing with rotational grazing on the basis of the total animal production obtained from dairy cattle on irrigated pasture.2. The same overall stocking rate was used for both treatments. Herbage surplus to grazing requirements at any time was conserved as hay and fed back to the appropriate group of cows at the end of the grazing season.3. The aim was to manage the area under each technique as efficiently as the technique per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1960
1960
1978
1978

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…
In an earlier experiment (Freer, 1959) it was found that the efficiency of year-round pasture utilization by dairy cows on irrigated pasture was no greater with a strip-grazing system (twice daily shifts) than with a rotational grazing technique (5-to 7-day shifts). The results of that experiment, in which both treatments were maintained at the same overall stocking rate, were discussed in relation to experiments of other workers in which differential stocking rates had been used.
…”
mentioning
confidence: 94%
“…
In an earlier experiment (Freer, 1959) it was found that the efficiency of year-round pasture utilization by dairy cows on irrigated pasture was no greater with a strip-grazing system (twice daily shifts) than with a rotational grazing technique (5-to 7-day shifts). The results of that experiment, in which both treatments were maintained at the same overall stocking rate, were discussed in relation to experiments of other workers in which differential stocking rates had been used.
…”
mentioning
confidence: 94%
“…Many reported experiments on management techniques provide little useful information because their designs neglected the facts that (a) a difference in stocking rate between the techniques under study will have an effect on production and thus confound the effect of the technique (Lucas and McMeekan, 1959;line, 1970), and (b) comparisons al stocking rates far below the optimum are unlikely to test the techniques and are of little practical interest. Comparisons between grazing systems, made at uniform stocking rates, have shown little differences between strip, rotational, and continuous grazing (Campling, et'-al., 1958;Freer, 1959; Line, I 9 OO). A general review of the subject was made by Wheeler (i960) who concluded "contrary to frequently expressed opinion, forms of rotational grazing per se, have not, in objectively conducted experiments proved appreciably more productive (either in terms of product per animal or per unit land) than continuous grazing" (P. 68).…”
Section: Fixed and Variable Stocking Ratesmentioning
confidence: 99%